The Effect of Essential Oil Types on The Physical Characteristics and Consumer Preference Level of Antiaging Body Lotion that Contain NLC-Coenzyme Q10 - Fransisca Dita Mayangsari; Khusnul Khotimah; Asyalafia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Lavender oil and lime oil contain linalool which has a relaxing effect. This oil has potential as a fragrance in antiaging body lotion products containing Coenzyme Q10 (CoQ10) in the Nanostructured Lipid Carriers System (NLC). This study aimed to analyzed the physical characteristics and consumer preference level for anti aging body lotion containing NLC-CoQ10. NLC-CoQ10 was prepared using the High Shear Homogenization method. For F1 (Formula 1), NLC-CoQ10 is mixed with a gel base and lavender oil. For F2 (Formula 2), the type of essential oil added is lime oil. These two forms when compared with F0 (Formula 0 = formula without essential oils). The physical properties observed included organoleptic, pH, homogeneity, spreadability, and viscosity. Organoleptic test and homogeneity were analyzed descriptively. While the pH, spreadability, and viscosity were analyzed using One Way Anova. In the preference level test, the aspect that is assessed is aroma. This test was analyzed statistically using the Univariate method. Based on the physical characteristic test, it is known that the three formulas have the same color, consistency, and homogeneity. The difference between the three formulas lies in their aroma. F0 is unscented; F1 has a lavender scent; F2 has a lime scent. The viscosity of the three formulas is also different but does not affect the spreadability value. Based on the aroma preference level test, it is known that F2 has the highest value. The type of essential oil affects the aroma and level of preference of the panelists. The most preferred formula is a formula containing lime oil. Keyword: Anti-aging; Body Lotion; Koenzim Q10; Lavender Oil; Lime Oil